Pengaruh Komitmen Organisasional terhadap Kepuasan Kerja - Ida Ayu Kade Asri Dwiyanti; I Wayan Bagia (Universitas Pendidikan Ganesha, 2020)
The research aimed to obtain an explanatory finding was tested on the effect of organizational commitment on job satisfaction at PT BPR Nusamba Kubutambahan. The research design used in this study was quantitative with assosiative appoarch. The subject of this research is the employee at PT BPR Nusamba Kubutambahan and the object of this research focuses on the variabels of organizational commitment and job satisfaction. The population used in this study amounted to 60 employees. The data were collected by questionnaire then analyzed by simple reggresion analysis. The result of this research shows that Organizational Commitmen partially influence on Job Satisfaction at PT BPR Nusamba Kubutambahan amounted to 82,8% with a large influence contribution is 68,6%.